Influence of Food (Chlorella vulgaris) Concentration and Temperature on the Population Dynamics of Brachionus calyflorus Pallas' (Rotifera) Isolated from a Subtropical Reservoir in México - Sarma, S.S.S.; Arévalo Stevenson, Raymundo; Nandini, S. (CIENCIA ergo-sum; Vol. 5 Núm. 1 (1998): CIENCIA ergo-sum (marzo-junio 1998), 2017)
In this study we have analyzed the population growth of the rotifer Brachionus calyciflorus subjected to different conditions of temperature (25° C and 30°C) and algal concentration (namely, 1.0 X 10^, 2.0 X 10^ and4.0 X 10^cells ml3). We found that peak population densities were reached at around day 6 at 30°C but between day 9 to 13 at 25°C. The lowest r value recorded in the study was 0.30d+-0.03 at a food concentration of 1X106 cells ml at 25°Cand the highest population growth rate (0.47±0.01) at a food concentration of 4X10(6) cells mil(3) at 25°C. Both temperature and food concentration had a significant impact on the maximum population density reached, as well as the time necessary to reach the average peak abundance or the rate of growth per day (r).